Cemitério é lugar de criança? a visita guiada ao Cemitério Consolação como recurso para abordar a educação sobre a morte nas escolas - Maeda, Tatiane Sayuri (2017)
The present qualitative research aimed to understand how teachers from the city of São Paulo perceive the matter of education about death, from the experience of taking their students to a guided visit to Consolação Cemetery. A focus group with 9 participants was formed, with teachers who work with first and second grade students of municipal public elementary school, who had had this experience a month before the focus group had it. The instruments used were field observation of the school group which had a guided visit to Consolação Cemetery and a semi-structured interview by means of focus group. The collected material was analysed by the Bardin (2016) technique of content analysis, allowing identification of the categories: fear of death; sociocultural and religious context; participation in funeral ceremonies; meaning of the cemetery; effects of childhood experiences in the adult life; bereavement; communication about death at school; school visit to the cemetery; Zippy‟s Friends Program; students learning; pedagogy trainees learning; education on death at school. The observation has shown that students and teachers were participative and interested in thinking about the topic of death, having explored the cemetery as a place for learning. Teachers perceived the education on death as important at school and that they can also use their past personal childhood experiences with loss and death to help sympathise with the child‟s pain, as well as validate their perceptions and child‟s bereavement acknowledge. The results show that some children would ask questions based on what they had learnt in the classroom, in a previous project, while the teachers training indicate that the visit to the cemetery was an enabler for the appreciation of the idea of including the death topic at school, and the importance of observing the student‟s emotional issues in the learning process